2002
DOI: 10.1177/112070000201200202
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tribological Performance of 231 Metal-On-Metal Hip Articulations

Abstract: 231 cobalt-chromium metal-on-metal (METASUL design) retrieved articulations (297 retrieved components) were examined for their in vivo wear behaviour. A running-in period of about one year is observed where the in vivo wear rate for the whole articulation is approximately 35 m/year. After this running-in period, the measured in vivo wear rate of the whole articulation decreases to about 5 m/year. The metal-on-metal articulation can be considered as a very low wear articulation system. The combination of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 2 publications
3
43
0
Order By: Relevance
“…In this study, implants made of the same cast alloy to the same specifications and by the same manufacturer (Wright Medical Technology, Arlington, Tennessee) were selected to avoid confounding factors inherent to the metallurgy of the component alloys. Overall, this study supported the results of a large clinical retrieval study, suggesting that a run-in wear regime might occur in vivo for some six to thirty-six months 41 . Other studies that have described particles with varying proportions of cobalt, ranging from approximately that of the original alloy material (about 57%) to zero, had interpreted this reduction as an indication of in vivo corrosion 43 .…”
Section: Muñoz and Mischlersupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, implants made of the same cast alloy to the same specifications and by the same manufacturer (Wright Medical Technology, Arlington, Tennessee) were selected to avoid confounding factors inherent to the metallurgy of the component alloys. Overall, this study supported the results of a large clinical retrieval study, suggesting that a run-in wear regime might occur in vivo for some six to thirty-six months 41 . Other studies that have described particles with varying proportions of cobalt, ranging from approximately that of the original alloy material (about 57%) to zero, had interpreted this reduction as an indication of in vivo corrosion 43 .…”
Section: Muñoz and Mischlersupporting
confidence: 86%
“…It should, however, also be noted that the very short-term implants were revised for early clinical complications (e.g., dislocation or heterotopic ossification). The wear mechanisms and the wear rates might thus have been different and possibly contributed to the differences observed in the particle characteristics, especially considering that the volumetric wear of retrievals reported in the literature has suggested that the initial wear rates should be high 41,42 . As such, it can be concluded that any differences between original and more current metal-onmetal implant designs would probably be determined by the overall implant survival time rather than by differences in particle characteristics themselves 38 .…”
Section: Muñoz and Mischlermentioning
confidence: 99%
“…The study of retrievals [42] confirmed the tribological qualities of the bearings and backed the run-in phenomenon.…”
Section: Metal-on-metal: Episodesupporting
confidence: 53%
“…Clinical studies have shown that a 98.6-99% survival rate could be expected ten years after a contemporary MOM hip replacement with a near absence of osteolysis [4,5]. Also, a low amount of wear on retrieved implants and in vivo has been reported [20,21,23], confirming preliminary hip simulator tests [24] and former clinical data [15,22]. However, early aseptic failure associated with immunologically determined tissue reactions characterised by intense diffuse and perivascularly lymphocytic infiltration suggests that metal hypersensitivity was involved in the pathogenesis of aseptic loosening [10,17,26].…”
Section: Introductionmentioning
confidence: 99%
“…Wear measurement was carried out on a coordinatemeasuring machine (CMM5, SIP, Geneva, Switzerland) with a spatial resolution of <1 μm [20] for explants originated from patient 2. The precision of the wear measurements was estimated to be ±2 μm.…”
Section: Analysis Of Wear and Bearing Surfacesmentioning
confidence: 99%